2005
DOI: 10.1021/jf048310e
|View full text |Cite
|
Sign up to set email alerts
|

Ankaflavin from Monascus-Fermented Red Rice Exhibits Selective Cytotoxic Effect and Induces Cell Death on Hep G2 Cells

Abstract: Monascus-fermented red rice has traditionally been used as a natural food colorant or food preservative of meat and fish for centuries. Recently, it has become a popular dietary supplement due to many of its bioactive constituents being discovered. Commercial Monascus-fermented red rice was used in this study. According to the cell-based cytotoxicity assay, a compound with selective cytotoxicity was found and identified as ankaflavin. Ankaflavin was found to be toxic to human cancer cell lines Hep G2 and A549 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 25 publications
7
122
1
1
Order By: Relevance
“…[4][5][6][7][8] It has been demonstrated that ethanol extracts of Monascus-fermented rice exhibit antitumor effects on murine Lewis lung carcinoma cells in vivo. 3 The secondary Monascus metabolite ankaflavin (in contrast to monascin) exerted cytotoxic effects against human cancer cell lines in vitro, 16 indicating the potential of this secondary metabolite to prevent tumor progression. Such data offer new insight into complementary therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] It has been demonstrated that ethanol extracts of Monascus-fermented rice exhibit antitumor effects on murine Lewis lung carcinoma cells in vivo. 3 The secondary Monascus metabolite ankaflavin (in contrast to monascin) exerted cytotoxic effects against human cancer cell lines in vitro, 16 indicating the potential of this secondary metabolite to prevent tumor progression. Such data offer new insight into complementary therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that rR, rM and amino acid derivatives of pigments have antibiotic activities (Martinkova et al, 1999;Kim et al, 2006), and yM and yA have anti-tumor and immunosuppressive activities (Su et al, 2005;Akihisa et al, 2005b). Hence, most of them might potentially have some chemopreventive effects (Akihisa et al, 2005a;Knecht and Humpf 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, downstreaming of pure lovastatin from fermented medium is not required as fermented rice can be consumed directly after sterilisation and this can produce multiple therapeutic benefits, i.e. blood pressure lowering effects due to the presence of γ-aminobutaric acid (GABA) (Kohama et al 1987), antiinflammatory effects due to the presence of monascin (Lee et al 2006a), anticancer effects due to the presence of ankaflavin (Su et al 2005), antioxidant effects due to the presence of a free radical scavenger dimerumic acid (Taira et al 2002) including the lowering of serum lipids levels.…”
Section: Discussionmentioning
confidence: 99%